Effect of site-specific nutrient management on yield, profit and apparent nutrient balance under pre-dominant cropping systems of Upper Gangetic Plains - SINGH, V K; SHUKLA, A K; SINGH, M P; MAJUMDAR, K; MISHRA, R P; RANI, MEENU; SINGH, S K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted on a Typic Ustochrept soil at Project Directorate for Farming Systems Research Modipuram (2904’ N, 77046’ E, 237m asl), for three consecutive years (2007-08 to 2009-10) to evaluate the sitespecific nutrient management (SSNM) option against existing farmers fertilizer practices (FFP), state recommendation (SR), improved SR (ISR) (i.e. 25% higher than SR), and soil testing laboratory recommendation (STLR) in six predominant wheat based cropping systems of Upper Gangetic Plains, in terms of yield gain, economics, nutrient harvest index, soil fertility, and apparent nutrient balances. SSNM improved system wheat equivalent yield over SR, ISR, STLR and FFP by 19%, 8%, 17% and 29%, respectively. SSNM involved additional cost of Rupees 5 097 to 7 938 /ha over SR and FFP under different cropping systems but it gave higher added net return of Rupees 13 649 to 58 776 /ha and Rupees 25 030 to 68 980 /ha over SR and FFP, respectively. The output: input ratio and nutrient harvest index were also highest in SSNM. At the end of the experiment, soil available N, Olsen-P and available K content were either maintained or improved over its initial values in SSNM treatments, whereas these parameters declined or marginally increased over the initial contents under FFP and SR in 0-15 cm soil profile depth. After 03-crop cycles, apparent N and P balances were positive in most of the cropping systems and fertilizer treatments, except a negative N balance was noticed in pigeonpea [Cajanus cajan (L.) Millsp]â€“wheat (Triticum aestivum L.) and groundnut (Arachis hypogaea L.)â€“wheat systems under SR and SSNM treatments. The apparent K balances were negative across all the cropping systems and nutrient management options but the magnitude was lower under SSNM.